THE ROLE OF POPULAR CULTURE IN EDUCATION: TEACHING BY USING NOVEL - Elisa Betty Manullang (BAHAS, 2017)
Abstract           As one of the most important aspect in people’s life, education should be treated and improved well. It is so essential because education gives opportunity to have a better life. The process of a nation as fundamental was determined by education. The education is the most important thing that getting much a big attention full from society. Therefore people should think of any better ways to improve the quality of education. One of the ways is through popular education. As growing-trend culture, popular culture has been widely known especially by young people. Some relevant references have been gathered and the data analysis has shown that it is very acceptable to use novel, a part of popular culture to teach. This teaching technique can be used to teach morality and language skill at the same time. Thus in this novel will describe the contrastive of how main characters faced and solved household conflict both in Western-Nothingham and Malang-Java. Therefore education institution should be able to accommodate this sistem in order to succeed in educating specially morality education. Key words: Popular Culture, Morality, Novel, Language, Education